Respuesta :

Answer:

x=58/3

Step-by-step explanation:Simplify \frac{6}{14}

​14

​​6

​​  to \frac{3}{7}

​7

​3

​​ \frac{3}{7}=\frac{7}{x-3}

​7

​​3

​​ =

​x−3

​​7

​​ Multiply both sides by x-3x−3

\frac{3}{7}(x-3)=7

​7

​​3

​​ (x−3)=7

Simplify \frac{3}{7}(x-3)

​7

​3

​ (x−3) to \frac{3(x-3)}{7}

​7

​​3(x−3)

​​ \frac{3(x-3)}{7}=7

​7

​​3(x−3)

​​ =7

Multiply both sides by 77

3(x-3)=7\times 73(x−3)=7×7

Simplify 7\times 77×7 to 4949

3(x-3)=493(x−3)=49

6 Divide both sides by 33

x-3=\frac{49}{3}x−3=

​​​  Add 33 to both sides

x=\frac{49}{3}+3x=3

​49​​ +3

Simplify {49}{3}+3

​3

49​​ +3 to {58}{3}

​x=58/3​​